Cognitive and motor skill competence are different: results from a prospective randomized trial using virtual reality simulator and educational video in laparoscopic cholecystectomy - Yang, Cui; Sander, Felix; Helmert, Jens R.; Weiß, Christel; Weitz, Jürgen; Reißfelder, Christoph; Mees, Soeren Torge (The surgeon, 2023)
Background and purpose - Cognitive transfer represents an important issue in surgical education. It is essential for the acquisition of competence, such as decision making and error avoidance. This randomized study aims to compare the effectivity of cognitive transfer by observing the surgery versus using modern virtual reality simulators for learning a laparoscopic cholecystectomy. - Method - This was a prospective, randomized, single centre study. 40 medical students from a university hospital, a tertiary care teaching institution, were enrolled. After a short introduction of laparoscopic cholecystectomy, they were randomized into two groups (video group and simulator group). In the video group, participants watched the step-by-step educational video twice. In the simulator group, participants underwent training using the virtual reality simulator, including tutorial procedural tasks of laparoscopic cholecystectomy as well as a complete cholecystectomy on the simulator. After the training, cognitive competence including decision making and error awareness was assessed using a questionnaire. - Results - In the most critical step of laparoscopic cholecystectomy, “Dissection in Calot's triangle”, as well as in the aspect of planning next step, the video group was superior significantly (P = 0.038 and P = 0.04). No significant differences concerning the recognition of critical anatomical structures, choosing the necessary instruments as well as error awareness were found. - Conclusions - Learning by watching a high-quality educational video is more effective in acquiring the cognitive competence to combine learned single tasks. Traditional learning means as watching educational videos and modern, sophisticated VRS should be deployed complementarily to establish cognitive and motor competencies separately.